ASPEK PENDIDIKAN KELUARGA DALAM NOVEL IBUK KARYA IWAN SETYAWAN DAN PEMANFAATANNYA SEBAGAI ALTERNATIF MATERI PEMBELAJARAN APRESIASI SASTRA DI SMA KELAS XII - Rahayu, Nurul Wiji (Lingua Skolastika, 2018)
The family education without waiting to be dragged an absence of due time as well as to have a close relation betweenof parents and children . The family on education mother has the role of most important against education level of the children.A novel “Ibuk” chosen as an object for study ibuk figures in a lift of degrees family life the better by means of community givesgreat priority to education for her children although obstructed it is an economic problem. The formulation of a problem in thisresearch is (1) bridge but intrinsic element in a novel Ibuk the work of iwan setyawan which includes the theme and thecommunity figures ? ; (2) How are aspects of education the family contained in a novel Ibuk the work of Iwan Setyawan?; (3) How are the form of the utilization of novel Ibuk the work of Iwan Setyawan as an alternative learning material in high schoolclass XII?. The design of this study is deskriptif-kualitatif. Research data sources novel was ibuk and the syllabus. The researchresults show intrinsic element in the form of the theme of tenacity or struggle ibuk to bring his sons in a better life. Aspects ofeducation in a novel Ibuk family .The family pendidkan covering (1) Personality which liable to be the basis for child is ableto and conceal the family to live a good life, (2) Moral education form children better personal .( 3 ) social education play acritical role upon a child in interact in the community . The use of research results as an alternative matter learning literature inhigh school class xii, the curriculum 2013, Competence 3.3 analyze the text novel either through orally or in writing.Theimplementation of the teaching trying to understand explanation for the intrinsic ( theme and figure ) figures and aspects ofeducation family. Students are required to analyse the intrinsic ( theme and figure) figures and family aspek-aspek education ina novel ibuk and presented the results of the job.